On the continuity of principal eigenvalues for boundary value problems with indefinite weight function with respect to radius of balls in ℝN - Ghasem Alizadeh Afrouzi (International Journal of Mathematics and Mathematical Sciences)
We investigate the continuity of principal eigenvalues (i.e., eigenvalues corresponding to positive eigenfunctions) for the boundary value problem −Δu(x)=λg(x)u(x), x∈BR(0);u(x)=0, |x|=R, where BR(0) is a ball in ℝN, and g is a smooth function, and we show that λ1+(R) and λ1−(R) are continuous functions of R.